Relevance of Grade 1 Gray‐Scale Ultrasound Findings in Wrists and Small Joints to the Assessment of Subclinical Synovitis in Rheumatoid Arthritis. Issue 7 (2nd July 2013) - Witt, Matthias; Mueller, Felix; Nigg, Axel; Reindl, Christiane; Leipe, Jan; Proft, Fabian; Stein, Nicola; Hammitzsch, Ariane; Mayer, Stefan; Dechant, Claudia; Schulze‐Koops, Hendrik; Grunke, Mathias
Abstract : Objective: To investigate the clinical relevance of grade 1 findings on gray‐scale ultrasound (GSUS) of the joints in patients with rheumatoid arthritis (RA). Methods: We examined the wrists and small joints of 100 patients with early or established RA and 30 healthy controls, using GSUS and power Doppler ultrasound (PDUS). Independent clinical assessment of all joints for tenderness and swelling according to the European League Against Rheumatism examination technique was performed. Joints with grade 1 findings on GSUS were identified, and associations with swelling, pain, and findings on PDUS were assessed. Grade 1 findings on GSUS in patients with early RA were reassessed after 6 months of antirheumatic treatment. Results: Grade 1 results represented the majority of all GSUS findings in patients with RA and were also frequently recorded in healthy controls. Grade 1 GSUS findings were not associated with tenderness, swelling, or positive results on PDUS. In comparison to joints with grade 2 and grade 3 findings on GSUS, joints with grade 1 findings were less likely to respond to treatment. Conclusion: The present results indicate that grade 1 findings on GSUS have limited clinical relevance.